Positive Value of Reog Kendang for Tulungagung Residents - Annisa, Fitriyani (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This article aims to describe the positive values of Reog Kendang, which is one of the traditional arts of Tulungagung Regency, for the lives of the people of Tulungagung. This article was written using a literature review method. Literary sources were searched using Google Scholar with the keyword Reog Kendang. The criteria for literary sources used are those published in 2014-2024. Based on the literature collected, results were obtained showing that Reog Kendang as one of Tulungagung's cultural heritage has had various positive impacts in the fields of culture, economics, sports and politics. There are many positive values such as cooperation, responsibility, discipline, mutual respect, and a sense of love for the homeland that is felt through the existence of Reog Kendang art. By realizing the existence of Reog Kendang as a valuable cultural heritage, it is hoped that regional culture as the root of national culture will not be timeless or eroded by foreign culture.